MUTYH Gene Mutations and Breast Cancer Risk: A Focus on Southern Punjab, Pakistan - Aisha Murtaza (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Worldwide prevalence of breast cancer, a global health concern, varies and is impacted by genetic, environmental, and cultural variables. The connection between MUTYH gene mutations, environmental exposures, and breast cancer risk in Southern Punjab, Pakistan, is the main topic of this review. It takes a complete approach to look at the molecular features of MUTYH, describe the study process, present the results, and evaluate the ramifications. The review begins with a discussion of the occurrence of breast cancer worldwide, highlighting geographical differences that highlight the importance of genetics and environment. The discussion then turns to MUTYH's function in DNA repair and how particular mutations can affect a person's vulnerability to breast cancer. While recognizing inherent limits, the study methodology section goes into detail on data collecting, analysis methods, and ethical considerations. The results show how common MUTYH mutations are in the research population and how they are related to the risk of developing breast cancer. Potential genetic-environment interactions are highlighted in the discussion, particularly with regard to pesticide exposure. Implications place a strong emphasis on individualized interventions, environmental awareness, and improved healthcare systems for preventing breast cancer. The study's clinical, public health, and research implications is emphasized in the conclusion, which also makes recommendations for future research into the intricate interactions between genetics and environment. In conclusion, this analysis sheds light on the complex interactions between MUTYH gene mutations, environmental factors, and the risk of breast cancer in Southern Punjab. It advances our knowledge of the genesis of breast cancer and provides guidance for tailored treatment plans and future research by integrating viewpoints from the fields of genetics, epidemiology, and public health.